Question #2dc91

2 Answers
Feb 1, 2018

The third person will have to pay 1/6 of the cost.

Explanation:

Let the total cost be x
One of the three agrees to pay 12x, and other agrees to pay 13x
So, the amount remaining to be payed will be:

x12x13x

Equating the denominators:

=x(66)12(33)x13(22)x

=6x3x2x6

=x6

So, the third person will have to pay 1/6 of the cost.

Feb 1, 2018

16

Explanation:

the total cost can be represented by 1

adding the fractions 12+13

the lowest common multiple of 2 and 3 is 6

12+13=(12×33)+(13×22)=36+26=56

third person has to pay 156=6656=16

third person pays 16 of the cost